Webcam-use in the NICU-setting from the perspective of Health Care Professionals and its implication for communication with parents - Stümpel, Johanne; Dörrhöfer, Annika; Mantell, Pauline; Jannes, Christiane; Reimer, Alinda; Woopen, Christiane (Frontiers in Communication, 2023)
In Germany, a growing number of neonatal intensive care units (NICUs) are equipped with webcams. The utilization of webcams in the NICU is gaining greater attention and the impact of this technology can be manifold. However, there has been no definite understanding of its impact. We will highlight the webcam's implications on the communication between parents and Health Care Professionals (HCPs) in German NICUs. Methods 20 interviews were conducted with HCPs from three German NICUs between December 2019 and August 2020 according to a qualitative research design. Seven out of them had no webcam experience, whereas for 13 of them, webcam-use is part of their working routine. Interviews were analysed following Kuckartz' (2018) thematic analysis. Findings were assessed in accordance with the NICU Communication Framework of Wreesmann et al. (2021).HCPs consider the webcams as a beneficial addition to the interaction of parents with their infants, as well as the HCP-parent interaction. At the same time, HCPs created new pathways of communication with parents via the webcam. Any negative effects feared by HCPs without webcam experience regarding the communication with parents, including a lasting shift of conversation away from the infant and towards more technical aspects of the webcams, but also an increase in phone calls from parents and an associated increase in workload, could not be confirmed by HCPs with webcam experience.The findings indicate that the implementation of webcams in German NICUs not only has an influence on the communication between parents and HCPs, but it expands communicative pathways. It can be stated that they support tailored communication but are not necessarily sufficient to account for all aspects themselves. The results of this study help to assess the impact of webcams on communication between parents and HCPs and should be applied to strengthen it within NICUs equipped with webcams.